Significant mixed layer nitrification in a natural iron‐fertilized bloom of the Southern Ocean. Issue 11 (20th November 2015) - Fripiat, F.; Elskens, M.; Trull, T. W.; Blain, S.; Cavagna, A. ‐J.; Fernandez, C.; Fonseca‐Batista, D.; Planchon, F.; Raimbault, P.; Roukaerts, A.; Dehairs, F.
Abstract: Nitrification, the microbially mediated oxidation of ammonium into nitrate, is generally expected to be low in the Southern Ocean mixed layer. This paradigm assumes that nitrate is mainly provided through vertical mixing and assimilated during the vegetative season, supporting the concept that nitrate uptake is equivalent to the new primary production (i.e., primary production which is potentially available for export). Here we show that nitrification is significant ( 40–80% of the seasonal nitrate uptake) in the naturally iron‐fertilized bloom over the southeast Kerguelen Plateau. Hence, a large fraction of the nitrate‐based primary production is regenerated, instead of being exported. It appears that nitrate assimilation (light dependent) and nitrification (partly light inhibited) are spatially separated between the upper and lower parts, respectively, of the deep surface mixed layers. These deep mixed layers, extending well below the euphotic layer, allow nitrifiers to compete with phytoplankton for the assimilation of ammonium. The high contributions of nitrification to nitrate uptake are in agreement with both low export efficiency (i.e., the percentage of primary production that is exported) and low seasonal nitrate drawdown despite high nitrate assimilation. Key Points: Little nitrate consumption in an iron‐fertilized bloom of the Southern Ocean Significant mixed layer nitrification Nitrate‐based primary production is mainly regenerated production